Making Distinctions on Autonomous Cultural Field: the Case of Small-scale Alternative Music Festival Organisers in Estonia - Mäe, Rene; Allaste, Airi-Alina (Studies of Transition States and Societies, 2011)
This article aims to give a sense of the activities of small-scale cultural practitioners in Estonia. Whereas Western societies experienced the powerful emergence of youth (sub)cultures and DIY ideology, as well as self-organised low scale cultural production in the 1960s, in Estonia all of these practices are relatively new and born over the last decades. This article discusses the Eastern European speciﬁ cs of (sub)cultural production. The main concepts of this study are ﬁ elds in cultural production and symbolic capital according to Pierre Bourdieu, with consideration of the recent elaborations in the ﬁ eld of (sub)cultural studies. Interpreting the interests, motives and attitudes that are the basis for the activities of the promoters, this paper addresses the subjects of mainstream/underground, independent/commercial and high culture/subculture, thereby contributing to the relevant discussion in subculture studies.The empirical part of the paper relies mainly on in-depth interviews conducted by the ﬁ rst author (2009), while the interviews conducted by the second author (2010) are supported by ﬁ eldwork on club cultures 2002-2003. The data have been analysed and systematised by qualitative data analysis methods, with the help of NVivo research software.While subcultures usually create symbolic boundaries using their distinctive style, music and ideological practices, according to this study, promoters tend to create ‘independent brands’ for the purposes of participation in the small-scale cultural ﬁ eld. These independent brands involve a mix of the promoters’ taste in music, which is communicated through the ‘brand’ to signiﬁ cant others (music critics, lay audience and friends), and constitute an important means for creating symbolic capital.